Microscopic study on the shape of pineal calcification of Bangladeshi cadavers (Journal of Dhaka Medical College, 2015)
Context: The degree of calcification increases from younger to older in human pineal gland and the morphology of pineal calcifications change with advancing age as well. The aim of the present study was to describe the microscopic features of the pineal calcifications and find out age related changes in a Bangladeshi population. Methods: A descriptive type of study was done in the Department of Anatomy, Dhaka Medical College, from July 2009 to June 2010, based on the collection of 60 human pineal glands from whole human brains of unclaimed dead bodies that were under postmortem examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. After collection of the pineal gland, those were divided into group A (15-45 years), group B (31-40 years), group C (41-50 years) and group D (>50 years). All the histological slides from different groups were observed under the light compound microscope and their shapes were noted down. Results: In group A, 53.33% were found to be round, 40% oval and 6.67% of irregular shape. In group B, there were 45.46% round, 40.90% oval and 13.64% of irregular shape. In group C, there were 75% of irregular shape, 21.47% mulberry shaped and 3.53% oval. In group D, there were 80.65% mulberry shaped and 19.35% of irregular shaped. Conclusion: Age related changes were found in morphological features of pineal calcification. In young adults, the shape of the pineal calcification remains round or oval. With increasing age, it becomes irregular and mulberry shaped. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21526 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 151-155